Exploring Student Readiness for AI-Assisted Learning: A Preliminary Study in Indonesian Universities - Happy Komikesari; Fijira Pasyah (CV. FoundAE, 2025)
This study examined the emerging educational challenge of students’ readiness for AI-assisted learning in Indonesian universities, focusing on how cognitive, technological, and affective factors shape their preparedness to engage with AI-supported instructional environments. Using a quantitative, cross-sectional survey design, data were collected from 189 undergraduate students across diverse academic programs using validated AI readiness scales administered through an online questionnaire. Descriptive and inferential analyses revealed moderate to high readiness levels overall, with prior exposure to AI tools showing significant associations with cognitive and technological readiness, while gender and study major did not produce meaningful differences. Effect sizes indicated that experiential familiarity contributed more strongly to readiness than demographic variables. These findings highlight the developmental need to strengthen AI literacy and equitable digital access in higher education. The study offers empirical insights to guide curriculum design, institutional policy, and future research on responsible and developmentally aligned AI integration.